A case of lipoprotein glomerulopathy with a rare apolipoprotein E isoform combined with neurofibromatosis type I - Takasaki, Satoshi (CEN Case Rep, 2018)
Lipoprotein glomerulopathy (LPG) is a rare inherited disease characterized by histopathological features of lipoprotein thrombi in dilated glomerular capillaries and type III like hyperlipoproteinemia with heterozygous mutation of the apolipoprotein (apo) E gene. We herein present the case of a 50-year-old woman with LPG complicated by neurofibromatosis type 1 (NF1). To the best of our knowledge, this is the first report of a case of LPG complicated by NF1. On the other hand, she had not only a heterozygous apoE-Sendai mutation, which is one of the most frequent apoE variants in LPG patients, but also a rare isoform of ApoE5 (Glu3Lys). Although apoE mutation has been recognized as having a principal role in the pathogenesis of LPG, some other factors are assumed to be present in the pathogenesis of LPG, because many asymptomatic carriers of apoE variants are recognized. The coexistence of NF1 or apoE5 (Glu3Lys) allele might play a role as an additional factor in the development of LPG.